IMPLIKASI HUKUM HILANGNYA KEWENANGAN PENYIDIKAN DAN PENUNTUTAN PIMPINAN KOMISI PEMBERANTASAN KORUPSI - Alwi, Helmi (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
The enactment of Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 was followed by various controversies, including changing the organizational structure of the Corruption Eradication Commission, then by eliminating the authority of the KPK leadership in terms of investigating and prosecuting as stated in Law Number 30 of 2002 in Article 21 paragraph (4), as well as paragraph (6) where the KPK leadership is no longer the highest person in charge of the anti-corruption agency. The authority for investigation and prosecution as well as the responsibilities of the KPK leadership must exist, where this is the main authority in eradicating corruption. Disclosure of corruption cases always begins with investigations, investigations, and prosecutions in terms of finding evidence and suspects as well as determining punishments to ensnare the perpetrators of corruption. Meanwhile, the authority for investigation and prosecution as well as the responsibilities of the KPK leadership are still needed so that the KPK leadership can directly order investigators and public prosecutors who previously came from the Police and Prosecutors' agencies so that efforts to eradicate and prevent corruption can run well. The problem that can be raised is how to regulate the authority of the KPK leadership in investigation and prosecution, then what are the legal implications of the loss of authority to investigate and prosecute KPK leaders. Using normative legal research methods through statutory approaches and conceptual approaches, with prescriptive analysis techniques. The loss of authority and responsibility of the KPK leadership as investigators and public prosecutors can have implications for the loss of effective control of the KPK leadership in investigations and prosecutions. Then it can slow down efforts to eradicate corruption because the control of eradicating corruption is no longer directly with the KPK leadership or it can even stop the investigation and prosecution process. The Supervisory Board has a higher position than the KPK leadership, then the Supervisory Board is also given broader duties and authority from the KPK leadership related to law enforcement even though in carrying out the duties of the KPK institution it is the KPK leadership, but the authority and responsibility of the KPK leadership have turned to the Supervisory Board.